The subjective well-being via virtual worlds experience - Photiadis, Thomas; Zaphiris, Panayiotis (My University, 2016)
The current paper focuses on 3D subjective well-being through the study experience in Second Life, involving appraisal methods. It focuses on the determination of users' emotional profiles, pre and post Second life experience. It investigates, also, the emotional stimuli during 3D experience. Based on quantitative and qualitative analysis, this study gives the description of users' 3D emotional profile through the statistical analysis before and after 3D participation, and specifies the type of caused emotional stimuli during virtual immersion.
Keywords: Emotions; Second Life; 3D Experience; Mood; Need; Appraisal Theories